47. KNOWLEDGE AND ATTITUDES REGARDING E-CIGARETTES AMONG CA MAU MEDICAL COLLEGE STUDENTS IN 2025 (Vietnam Journal of Community Medicine, 2025)
Objective: To determine the proportion of students with accurate knowledge and appropriate attitudes regarding the harmful effects of e-cigarettes at Ca Mau Medical College in 2025, and to identify associated factors.Method: A cross-sectional descriptive study was conducted among 794 students from February to March 2025.Results: The proportion of students with accurate knowledge about e-cigarettes was 78.71%, and 72.54% had appropriate attitudes. Factors associated with accurate knowledge included being female (OR = 1.98), residing in urban areas (OR = 1.94), and having academic performance rated as good or higher (OR = 2.42). Similarly, appropriate attitudes were associated with being female (OR = 1.45), urban residence (OR = 1.49), and good academic performance or higher (OR = 1.59), with all p-values < 0.05.Conclusion: A relatively high proportion of students demonstrated accurate knowledge and appropriate attitudes toward e-cigarettes. However, misconceptions and inappropriate attitudes still exist among a portion of the student population.
Keywords: Knowledge; attitude; electronic cigarettes.